Stress and coping strategies among adolescents in private school, Chitwan, Nepal - Bhattarai, B; Maskey, S; Lopchan, M (Journal of Chitwan Medical College, 2017)
Changing emotional and physical status along with increasing social, family and academic pressure adolescents experience stress and their coping abilities determine the outcome. The objective of the study was to find out the level of stress and coping strategies among adolescents studying at Skyrider Higher Secondary English Boarding School, Ratnanagar-12, Chitwan. A descriptive cross-sectional research design was used in which a total of 50 adolescence studying in grade 9 and 10 were selected by using non- probability purposive sampling technique. The study findings revealed that the mean age of respondents was 15.26 ± 0.96, 48% respondents had high level of stress. Statistically, there was significant association between respondents’ level of stress and sex (P= 0.025), type of residence (P=0.049) and father’s education level (P= 0.045). “Investing in close friends” is the most common and “Avoiding” is the least common coping strategy used by adolescents. Overall study concluded that the adolescents has high stress level whereas as they use various coping strategies.